Perirenal fat thickness is an independent predictor for metabolic syndrome in steatotic liver disease - Jong Wook Choi; Chul-min Lee; Bo-Kyeong Kang; Mimi Kim (Scientific Reports)
Abstract The objective of our study is to measure perirenal fat thickness using MRI in individuals with steatotic liver disease and investigate the relationship between perirenal fat thickness and metabolic syndrome. This retrospective study included consecutive patients with steatotic liver disease who underwent magnetic resonance imaging-proton density fat fraction from October 2018 to February 2020. Among them, patients with crossed fused kidneys or who underwent nephrectomy were excluded. The metabolic abnormalities were reviewed; presence of hypertension, type 2 diabetes, abdominal circumference, triglyceride, and high-density lipoprotein. Perirenal fat was measured in four directions in both kidneys and the total sum of them was calculated. A total of 250 patients (140 males and 110 females) were included. Perirenal fat thickness showed a moderate correlation with waist circumference, creatinine, and hepatic fat fraction (all p < 0.001). Perirenal fat thickness was significantly higher in patients with metabolic syndrome than in patients without (76.8 mm vs. 65.1 mm, p = 0.004). In multivariable regression analysis, the group with high perirenal fat thickness had as significantly higher odd ratio of 2.71 compared to the low group. The perirenal fat thickness is independently associated with metabolic syndrome in patients with steatotic liver disease.